2001
DOI: 10.1046/j.1365-3083.2001.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Age‐Related Changes of Immune Function in Mice

Abstract: Understanding of the genetic basis of normal and abnormal development of the immune response is an enormous undertaking. The immune response, at the most minimal level, involves interactions of antigen presenting cells (APCs), T and B cells. Each of these cells produce cell surface and soluble factors (cytokines) that affect both autocrine and paracrine functions. A second level of complexity needs to consider the development of the macrophage/monocyte lineage as well as the production of the common lymphoid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…One advantage of using the BXD RI strains as a model of tumor growth is that these cell lines are the focus of ongoing studies to identify the mechanisms underlying differences in immune responses 35. The present results lend further support to the concept that T cells can play critical roles in limiting tumor growth and mediating tumor regression.…”
Section: Discussionsupporting
confidence: 69%
“…One advantage of using the BXD RI strains as a model of tumor growth is that these cell lines are the focus of ongoing studies to identify the mechanisms underlying differences in immune responses 35. The present results lend further support to the concept that T cells can play critical roles in limiting tumor growth and mediating tumor regression.…”
Section: Discussionsupporting
confidence: 69%
“…50,51 We found that aged mice of all strains showed a highly significant (P Ͻ .001) decline of T cells in blood compared with younger animals of the same strain ( Figure 1). However, aged D2 mice showed a significantly (P ϭ .02) higher level of T cells (25.4% Ϯ 5.7%) compared with aged B6 (17.6% Ϯ 6.7%).…”
Section: Age-and Strain-related Changes In Myeloid Cells In Bloodmentioning
confidence: 87%
“…AKXD strains have been used to study a variety of diseases including murine lymphoma and glaucoma [24], [25]. The more widely used BXD strains have been used to understand the genetics of a variety of diseases and biological systems including aging, the immune system and iron regulation [26], [27], [28], [29], [30]. Much of this work has been made available through GeneNetwork (formerly WebQTL ) an on-line resource to study complex gene networks and phenotypes [31].…”
Section: Introductionmentioning
confidence: 99%